Pembangunan Sistem Pemesanan Koki dan Makanan Berbasis Web - Amirrulloh Acmad Kusaini Alkakim; Fajar Pradana; Bayu Priyambadha (Fakultas Ilmu Komputer (FILKOM), Universitas Brawijaya, 2018)
Predicate as the second largest city in East Java, Malang became one of the target of students to gain knowledge either from Java Island or outside Java Island. This is a problem for students especially who have different food tastes. In addition to the problem of different tastes of food turned out to make cuisine at an event such as fine dinning is also a problem for the owner of the event, especially for the owner of the event that cooks their own food because of the hassles. Therefore, the researcher makes the solution by making the information system of ordering food and the chef. Where in the selection of chefs using algorithm profile matching which has advantages in accordance with the issues raised by the tests that can run in accordance with the requirements that have been identified. This system is expected to overcome the problems that have been mentioned so that will improve the economy of small and medium-sized stalls and can reduce unemployment for lovers of cooking hobby that can channel his hobby into a work that makes money.